The German Ethical Culture Scale (GECS): Development and First Construct Testing - Tanner, Carmen; Gangl, Katharina; Witt, Nicole (Frontiers in Psychology, 2019)
Misconduct in organizations (such as fraud, stealing, deception, and harming others) is not only a matter of some “bad apples” but also related to the organizational context (“bad barrels”), which can facilitate either ethical or unethical behaviors. Given the financial crisis and recurring corporate ethics scandals, policymakers, regulators and organizations are interested in how to change their organizational cultures to enhance ethical behavior and to prevent further disasters. For this purpose, organizations need to better understand what strategies and factors of the organizational environment can affect (un)ethical behavior. However, to assess the corporate ethical culture, solid measures are required. Since there is an urgent need to have a German measure to promote research in German-speaking countries, this research developed and tested the German Ethical Culture Scale (GECS). Drawing on a prominent approach that has received much attention from scholars and practitioners alike, the GECS attempts to integrate the notion of compliance- and integrity-based ethics programs (with its focus on how to steer organizations) with the notion of ethical culture (with its focus on what factors inhibit or foster ethical behavior). Three studies with heterogeneous samples of German and Swiss employees and managers were conducted to develop, test and validate the multidimensional scale (total N > 2000). Overall, the studies provide first evidence of the measure’s construct, criteria-related and incremental validity. The paper concludes with a discussion of the strengths and weaknesses of the GECS and implications for future research.